2022
DOI: 10.1097/bot.0000000000002306
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Pubic Rami Fracture Morphology and Fixation to Pelvic Ring Stability in Type 1 Lateral Compression Injuries: A Biomechanical Cadaveric Study

Abstract: Background: Treatment of lateral compression type 1 (LC-1) injuries has historically been nonoperative with immediate weightbearing. However, management of these injuries remains controversial, with reports of displacement at follow-up for nonoperatively managed LC-1 fractures. The goal of our study was to determine the effect of superior pubic ramus fracture morphology and fixation construct on pelvic stability.Methods: Ten fresh-frozen cadaveric were transected into hemipelvises. Incomplete Denis type 1 sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Currently, there are conflicting views on what constitutes an unstable LC1 injury, with some authors basing their criteria on the degree of fracture displacement [ 22 ] and others on the patient’s pain, for example [ 12 ]. A recent cadaveric study also revealed that the displacement of LC1 injuries may be related to pubic rami fracture morphology with oblique pubic rami fractures being most susceptible to displacement over time [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Currently, there are conflicting views on what constitutes an unstable LC1 injury, with some authors basing their criteria on the degree of fracture displacement [ 22 ] and others on the patient’s pain, for example [ 12 ]. A recent cadaveric study also revealed that the displacement of LC1 injuries may be related to pubic rami fracture morphology with oblique pubic rami fractures being most susceptible to displacement over time [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…The treatment had been a headache for clinical orthopedics doctors [ 1 ]. The posterior pelvic ring beard 70% of the load of the whole pelvic ring, Posterior pelvic ring injuries such as sacroiliac joint dislocation and sacral fracture were often accompanied by vertical instability and rotational instability [ 2 ]. Therefore, early effective reduction and fixation is very necessary.…”
Section: Introductionmentioning
confidence: 99%
“…2,7–19 To better identify patients who may benefit from surgical fixation, many studies have investigated injury patterns and characteristics suggestive of instability. 2,10,20–23 In addition, examination under anesthesia (EUA) and stress radiographs have been used in evaluation of patients with minimally displaced injuries to determine the degree of dynamic displacement present to identify patients who may benefit from operative management. 5,6,12,18,24–29…”
Section: Introductionmentioning
confidence: 99%
“…2,[7][8][9][10][11][12][13][14][15][16][17][18][19] To better identify patients who may benefit from surgical fixation, many studies have investigated injury patterns and characteristics suggestive of instability. 2,10,[20][21][22][23] In addition, examination under anesthesia (EUA) and stress radiographs have been used in evaluation of patients with minimally displaced injuries to determine the degree of dynamic displacement present to identify patients who may benefit from operative management. 5,6,12,18,[24][25][26][27][28][29] With the reported advantages of reduced resource utilization, normalized force application, and standardized measurements, lateral stress radiographs (LSRs) have been routinely applied for the evaluation of minimally displaced LC1 injuries at our level 1 trauma center to guide management recommendations.…”
Section: Introductionmentioning
confidence: 99%